2017
DOI: 10.18632/oncotarget.15885
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a and miR-146b promote proliferation, migration and invasion of follicular thyroid carcinoma via inhibition of ST8SIA4

Abstract: Follicular thyroid carcinoma (FTC) is a more aggressive form of thyroid cancer than the common papillary type. Alpha-2,8-sialyltransferase (ST8SIA) family members are expressed in various cancers and may be associated with FTC progression. In this study, we measured ST8SIA family expression in two FTC cell lines with different invasive potentials (FTC-133 and FTC-238) and Nthy-ori 3-1 cell lines, as well as FTC and normal thyroid tissues. ST8SIA4 was downregulated in the highly invasive FTC-238 cells and FTC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…miR-146a and miR-146b have been shown to be upregulated and associated with adverse prognostic features, progression and invasion in papillary ( 60 ), follicular ( 61 ) and anaplastic ( 62 ) thyroid cancers. This effect may be mediated through associations with NF-KB ( 62 ), ST8SIA4 ( 61 ) or RARB ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a and miR-146b have been shown to be upregulated and associated with adverse prognostic features, progression and invasion in papillary ( 60 ), follicular ( 61 ) and anaplastic ( 62 ) thyroid cancers. This effect may be mediated through associations with NF-KB ( 62 ), ST8SIA4 ( 61 ) or RARB ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…however, the expression of miR-146a is significantly higher in thyroid follicular carcinoma (32,33) and oral carcinoma (34), and the downregulation of miR-146a expression can inhibit the malignant biological behaviors of tumor cells. In addition, the negative feedback mechanism associated with miR-146a is not applicable to all tumor cells (35).…”
Section: Discussionmentioning
confidence: 96%
“…The sialyltransferase ST8SIA4 is downregulated in invasive tumor cells and is also involved in EMT. 27,28 Therefore, we sought to determine whether ST8SIA4 is regulated by miR-146a. Bioinformatic analysis revealed a potential miR-146a binding site in the 3 0 UTR of ST8SIA4, and luciferase reporter assays confirmed that miR-146a can downregulate ST8SIA mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alpha-2,8-sialyltransferase 4 (ST8SIA4) is expressed in various cancer and may be associated with OSCC, and is regulated by miR-146a. 14 In the present study, we investigated the effect of miR-146a on proliferation, invasion and EMT in OSCC cells. We also investigated the effects of miR-146a on the expression of ST8 alpha-N-acetylneuraminide Alpha-2,8-sialyltransferase 4 (ST8SIA), which is an important regulator of EMT.…”
Section: Introductionmentioning
confidence: 99%